Medication Related Osteonecrosis of the Jaw: A Case Report and Review of Literature - Amisha Parekh; Pedro Tretto; Nicklaus Blue; Blake Dunaway; James Lott; Michael Roach; Rohan Jagtap (European Annals of Dental Sciences)

(untitled)
Medication-related osteonecrosis of the jaw is an adverse reaction caused by the use of antiresorptive antiangiogenic medication. The most commonly affected areas are posterior regions of mandible and maxilla. However, a simultaneous occurrence in both jaws is rarely observed. We present an interesting case of MRONJ affecting both jaws. A 47-year old female presented with pain and swelling in the left posterior region of the mandible. The patient’s medical history was significant for breast cancer with ongoing bisphosphonate therapy. Cone-beam CT (CBCT) confirmed the presence of an extraction socket at the site of complaint. There was evidence of a diffuse sclerotic bone reaction in the maxillary posterior region bilaterally. The mandible showed presence of diffuse sclerotic bone only in the left para-symphysis and posterior region in addition to association with a periosteal bone reaction in the left para-symphysis region. Considering these findings and a history of exposure to bisphosphonate medication, the final diagnosis was conclusive of MRONJ. Management was aimed at suppressing the symptoms of pain and infection. The present case study reinforces the importance of correlating clinical and radiographic findings. Early diagnosis of MRONJ may lead to a more conservative treatment approach, greatly improving the patient’s prognosis.Keywords: MRONJ, Cone-beam CT, breast cancer, bisphosphonate